The KURANG ENERGI KRONIS IBU HAMIL SEBAGAI FAKTOR RISIKO TERHADAP KEJADIAN STUNTING PADA BALITA (USIA 24-59 BULAN) DI WILAYAH KERJA PUSKESMAS WAY URANG KECAMATAN KALIANDA LAMPUNG SELATAN - Muhammad Abi Nubli; Sutarto Sutarto (CV. Jasa Sukses Abadi, 2023)
Stunting in infants is influenced by the history of nutrition mother like Less Energy Chronic (KEK). Lampung Province in 2018 had a prevalence of 27.3% had a case of short toddlers . The prevalence of South Lampung in 2018 has a prevalence of 43.01% of 42,971 people suffering from stunting .In the district of Urung Way itself which has the highest prevalence is the village of chess clans that is equal to 41.49%. The purpose of this study was to determine the prevalence of SEZ as a risk factor for the incidence of stunting under five (ages 24-59 months) in the Work Area of Way Urang Health Center in South Lampung Regency . This research is observational with case control method. Sample research is mothers who had infants aged 24 - 59 months in Region Work Puskesmas Way Urang to sample a number of 52 cases and 52 controls. This study uses the book Maternal and Child Health (MCH), and for statistical analysis a chi-square test is used. The results of the study distribution of frequencies history Less Energi Chronic (KEK) at the time of pregnancy, namely 32 mothers (30.8%) had a history of KEK and as many as 72 mothers (69.2%) did not have a history of Less Energy Chronic (KEK) during pregnancy and Less energy Chronic (KEK) mother pregnant as a factor of risk of occurrence of stunting in infants (age 24-59 months ) in Region Work Puskesmas Way Urang District South Lampung.